Mechanisms and Applications of Essential Oils as Natural Preservatives in Meat Products: A Review - Ulil Afidah; Riuh Wardhani; Swastika Dewi; Lutfi Purwitasari (Journal of Applied Food Technology, 2025)
The increasing global demand for meat products illustrates the importance of safe and effective preservation methods. Butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), and tertiary butylhydroquinone (TBHQ) are common synthetic preservatives that stop microbial growth and lipid oxidation. However, they have been linked to negative health effects. Consequently, natural alternatives such as essential oils (EOs) have gained attention due to their antimicrobial and antioxidant activities. Mechanistically, EOs disrupt microbial cell membranes, inhibit key metabolic enzymes, and scavenge free radicals that initiate lipid oxidation. This review discusses the mechanisms and applications of various essential oils as natural preservatives in meat and meat products. Essential oils, which are high in phenolic compounds, work by breaking down microbial cell membranes, stopping enzymatic systems, and neutralizing free radicals that cause oxidation. Several studies have demonstrated that essential oils (EOs) function as a promising natural preservative in meat products by utilizing specific mechanisms to enhance chemical, microbiological, and sensory quality. For instance, rosemary essential oil (REO), when integrated into vacuum packaging, effectively extends the shelf life of chicken meatballs by inhibiting microbial growth and scavenging free radicals to prevent lipid oxidation. Similarly, oregano essential oil (OEO) exhibits strong antimicrobial action against foodborne pathogens like Salmonella enteritidis and Escherichia coli in dried meat while enhancing sensory properties. In sausage products, nutmeg essential oil (NO) demonstrates its antioxidant capacity by significantly reducing lipid oxidation indicators such as thiobarbituric acid reactive substances (TBARS), suppressed mesophilic bacteria growth, and improved aroma stability during storage. Collectively, these findings confirm that essential oils represent promising natural preservatives that offer a safer multi-target alternative to synthetic additives, especially in the mechanism of cell membrane damage and lipid peroxidation inhibition.